Magnaporthe oryzae CK2 Accumulates in Nuclei, Nucleoli, at Septal Pores and Forms a Large Ring Structure in Appressoria, and Is Involved in Rice Blast Pathogenesis - Zhang, Lianhu; Zhang, Dongmei; Chen, Yunyun; Ye, Wenyu; Lin, Qingyun; Lu, Guodong; Ebbole, Daniel J.; Olsson, Stefan; Wang, Zonghua (Frontiers in Cellular and Infection Microbiology, 2019)
Magnaporthe oryzae (Mo) is a model pathogen causing rice blast resulting in yield and economic losses world-wide. CK2 is a constitutively active, serine/threonine kinase in eukaryotes, having a wide array of known substrates and involved in many cellular processes. We investigated the localization and role of MoCK2 during growth and infection. BLAST search for MoCK2 components and targeted deletion of subunits was combined with protein-GFP fusions to investigate localization. We found one CKa and two CKb subunits of the CK2 holozyme. Deletion of the catalytic subunit CKa was not possible and might indicate that such deletions are lethal. The CKb subunits could be deleted but they were both necessary for normal growth and pathogenicity. Localization studies showed that the CK2 holoenzyme needed to be intact for normal localization at septal pores and at appressorium penetration pores. Nuclear localization of CKa was however not dependent on the intact CK2 holoenzyme. In appressoria, CK2 formed a large ring perpendicular to the penetration pore and the ring formation was dependent on the presence of all CK2 subunits. The effects on growth and pathogenicity of deletion of the b subunits combined with the localization indicate that CK2 can have important regulatory functions not only in the nucleus/nucleolus but also at fungal specific structures as septa and appressorial pores.